Flexibilização do arcabouço regulatório vigente a partir do estudo e projeto de sistema híbrido eólico - fotovoltaico isolado - Araújo, Rafael Gonçalves Bezerra de (2008)
This study examines technical and regulatory aspects of hybrid systems for electricity generation, with emphasis on solar and wind resources, placed in isolation in the state of Bahia. The main purpose of the study is the design and installation of pilot isolated hybrid system and the main systems components with this configuration, presenting advantages and disadvantages. Additionally the paper examines the current regulatory framework and the possibility of its flexibility depending on the characteristics of continuity of the distribution of electrical energy, in terms of duration and frequency, required by the National Agency of Electric Energy - ANEEL. The work study to extend the service of electricity to remote areas within the brazilian universalization program, analyze the feasibility of establishing mechanisms of relaxation in the regulation of levels of continuity in the supply of electricity provided by wind photovoltaic hybrid system generation of electric power alone, called SHEFI (in portuguese). This study will discuss the definitions of the technical characteristics of hybrid systems and indices of continuity of service of electric energy (DEC, FEC, DIC, FIC and DMIC) to be required and regulated by ANEEL's Resolution 024. It also discusses the amount of energy released by the system. Questions are raised about the track between the gray SIGFI rules and systems connected to the network regulated by Resolutions 83 and 024 of ANEEL, respectively.